PENGEMBANGAN BAHAN AJAR GEOMETRI BERBASIS STEM UNTUK PEMBELAJARAN YANG EFEKTIF DI SMA - Permatasari, Eka Yunita; Mulbar, Usman (Universitas Batanghari Jambi, 2026)
This study was motivated by students’ low conceptual understanding of mathematics, as indicated by the results of the Programme for International Student Assessment (PISA), as well as mathematics instruction that remains abstract and lacks context. Therefore, the development of instructional materials capable of linking mathematical concepts to real-world situations requires innovation. The objective of this study is to create STEM-based instructional materials that meet valid, practical, and effective standards by using the Realistic Mathematics Education (RME) approach for the topic of curved-edged three-dimensional shapes in Grade 10 MIPA at SMA in Bone. This study is a research and development (R&D) project using the ADDIE model, which includes the analysis, design, development, implementation, and evaluation stages. The research subjects consisted of subject matter experts, design experts, teachers, and 10th-grade students. An abstract is often presented separately from the article, so it must be able to stand-alone. Data collection techniques included interviews, questionnaires, and achievement tests. The data obtained were analyzed using descriptive statistical techniques to assess the validity, practicality, and effectiveness of the developed instructional materials. This study is expected to produce STEM-based instructional materials that can enhance students’ understanding of geometric concepts through contextual and meaningful learning that utilizes local culture as a learning resource. Therefore, the developed instructional materials can serve as an innovation.